Exploring the Dynamics of Urban Gentrification: A Human Geographical Perspective. e2322355 - Bappa Hosen (Terr@ Plural, 2023)
Urban gentrification, a process of neighborhood transformation driven by complex interplays of socioeconomic forces, policy interventions, and cultural shifts, has become a prominent focal point in contemporary human geography. This research article offers a comprehensive human geographical exploration of gentrification’s dynamics, impacts, and implications. This study delves into the multifaceted dimensions of gentrification within urban landscapes through a synthesized analysis of existing literature, empirical case studies, and theoretical frameworks. The article begins by elucidating the diverse drivers that initiate and perpetuate gentrification, including rising property values, shifts in consumer preferences, and economic restructuring. Subsequently, the spatial manifestations and social impacts of gentrification are examined, emphasizing the displacement of existing communities, altered neighborhood identities, and the transformation of urban landscapes. The role of public policies in shaping gentrification trajectories is then interrogated, highlighting the influence of urban planning, housing policies, and zoning regulations on the process. Furthermore, the article addresses the contestations and resistances that gentrification often engenders. It examines the strategies marginalized communities and grassroots organizations adopted to challenge the displacement of long-standing residents and the erosion of local cultures. Building upon these insights, the study advocates for inclusive and equitable urban development strategies prioritizing social justice principles and community well-being. this research contributes to a holistic understanding of urban gentrification from a human geographical standpoint. By unraveling the intricate relationships between space, society, policy, and power dynamics, this article emphasizes the need for nuanced approaches to address the challenges posed by gentrification and to foster sustainable and vibrant urban landscapes that accommodate diverse populations and preserve local identities